1988
DOI: 10.1136/emj.5.2.59
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination in United Kingdom accident and emergency departments.

Abstract: SUMMARYHepatitis B vaccination is not widespread amongst staff in accident and emergency departments in the United Kingdom. The results of a survey of departments training senior registrars reveal that unfounded fears concerning the safety of the vaccine are responsible for the low uptake. The need for vaccination, cost, medicolegal aspects and future developments are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
3
2
1
Order By: Relevance
“…Furthermore, the association between 'concern about the efficacy of the Hepatitis B vaccine' and the uptake of vaccination would become significant (F=4-835, P=0-03, Table 3) if the comparison was hased on the vaccinated and unvaccinated group and excluded the incompletely vaccinated group. This result was consistent with the finding that 'concern regarding vaccine efficacy' was of paramount importance in the decision to be vaccinated in other studies (Israsena et aL 1992, Mckenzie 1992, Spence & Dash 1990, Alexander et al 1990, Harward et al 1988, Heyworth 1988, Bodenheimer et al 1986, Kwon et al 1984.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the association between 'concern about the efficacy of the Hepatitis B vaccine' and the uptake of vaccination would become significant (F=4-835, P=0-03, Table 3) if the comparison was hased on the vaccinated and unvaccinated group and excluded the incompletely vaccinated group. This result was consistent with the finding that 'concern regarding vaccine efficacy' was of paramount importance in the decision to be vaccinated in other studies (Israsena et aL 1992, Mckenzie 1992, Spence & Dash 1990, Alexander et al 1990, Harward et al 1988, Heyworth 1988, Bodenheimer et al 1986, Kwon et al 1984.…”
Section: Discussionsupporting
confidence: 91%
“…The completed vaccination rate was 69-2% in this study which, in general, was higher than that identified in earlier studies (22-69%) (Briggs & Thomas 1994, Murata & Young 1993, Mckenzie 1992, Israsena et al 1992, Scapa et al 1989, Harward et al 1988, Heyworth 1988, Kwon et al 1984, Triger 1984. In spite of this, 31-8% of respondents failed to complete the full vaccination schedule.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…This finding is congruent to literatures respectively from India, 9 Georgia, 31 and England. 32 It also agrees with a study that described "[T]he main reason for declining vaccination was the risk of vaccine side effects." 33 The aftermath of a person's perceived susceptibility to the…”
Section: Discussionsupporting
confidence: 87%